Mapping of protein-protein interactions of E. coli RNA polymerase with microfluidic mechanical trapping. - Steven R Bates (PLoS ONE, 2014)
The biophysical details of how transcription factors and other proteins interact with RNA polymerase are of great interest as they represent the nexus of how structure and function interact to regulate gene expression in the cell. We used an in vitro microfluidic approach to map interactions between a set of ninety proteins, over a third of which are transcription factors, and each of the four subunits of E. coli RNA polymerase, and we compared our results to those of previous large-scale studies. We detected interactions between RNA polymerase and transcription factors that earlier high-throughput screens missed; our results suggest that such interactions can occur without DNA mediation more commonly than previously appreciated.